Optical glass, optical element and optical instrument

The optical glass with a specific composition addresses the challenge of achieving low transition temperatures and suitable densities, enabling the production of high-performance optical components with the desired refractive index and Abbe number.

JP2025054264AActive Publication Date: 2025-04-07CDGM OPTICAL GLASS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024163987
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-25
Filing Date
2024-09-20
Publication Date
2025-04-07
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

Existing optical glasses with refractive indices of 1.45-1.51 and Abbe numbers of 66-74 face challenges in achieving low transition temperatures and suitable densities for precision molding, which is essential for manufacturing high-performance optical components.

Method used

The development of optical glass with specific compositions, including 50-70% SiO2, 2-18% B2O3, 10-30% K2O, and F content above 3% to 20%, along with other oxides, to achieve the desired refractive index, Abbe number, and reduced transition temperature.

Benefits of technology

The optical glass achieves a refractive index of 1.45-1.51, an Abbe number of 66-74, a transition temperature below 490°C, and a density of 2.70 g/cm³, making it suitable for precision molding and high-performance optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054264000001
    Figure 2025054264000001
  • Figure 2025054264000002
    Figure 2025054264000002
  • Figure 2025054264000003
    Figure 2025054264000003
Patent Text Reader

Abstract

To provide an optical glass that has a lower transition temperature and a lower density while having a desired refractive index and a desired Abbe number.SOLUTION: The present invention provides an optical glass that includes the following components, in percentage by weight: 50-70% of SiO2, 2-18% of B2O3, 10-30% of K2O, and more than 3% to 20% or less of F, where SiO2 / (K2O+F) is 1.2-4.5.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical glass, and in particular to an optical glass having a refractive index of 1.45 to 1.51 and an Abbe number of 66 to 74, as well as an optical component and an optical device manufactured therefrom. [Background technology]

[0002] In recent years, with the development of optoelectronic information, digital displays, etc., there is a demand for optical components used in optical systems to be smaller, lighter, and more powerful. Currently, precision molding methods such as direct press molding and secondary press molding are the mainstream for manufacturing optical components, which can reduce raw material consumption, labor costs, material costs, and environmental pollution, and this technology allows for mass production of aspheric components at low cost. The so-called precision stamping refers to stamping a glass preform with a high-precision mold of a predetermined product shape at a certain temperature and pressure, thereby obtaining a glass product with the final product shape and optical function. Precision stamping technology can be used to manufacture various optical components such as spherical lenses, aspheric lenses, prisms, and diffraction gratings.

[0003] When precision stamping is performed, the glass preform needs to be press molded at high temperatures (usually glass transition temperature 20-60°C or higher) in order to transfer the high-precision mold surface to the finished glass product. In this case, the mold surface is easily oxidized and eroded under high temperature and pressure, even in protective gas. In order to extend the life of the mold and prevent damage to the mold due to high temperature environment, it is necessary to lower the molding temperature, and therefore the transition temperature of the optical glass used for stamping needs to be as low as possible. Chinese Patent Application No. CN101300202A discloses optical glass with a refractive index of 1.45-1.65 and an Abbe number of 65 or more, and the transition temperature needs to be further lowered. Chinese Patent Application No. CN108529874A discloses optical glass with a refractive index of 1.42-1.53 ​​and an Abbe number of 55-98, which has a low transition temperature but a relatively high density and is not suitable for the requirement of weight reduction. Summary of the Invention

[0004] The technical problem that the present invention aims to solve is to provide an optical glass having a refractive index of 1.45-1.51 and an Abbe number of 66-74.

[0005] In order to solve the technical problem, the present invention uses the following technical solutions:

[0006] (1) An optical glass having components, by weight percentage, of 50-70% SiO2, 2-18% B2O3, 10-30% K2O, and more than 3% but not more than 20% F, with SiO2 / (K2O+F) being 1.2-4.5.

[0007] (2) Its components are, by weight percentage, 0-5% Al2O3, and / or 0-2% Nb2O5, and / or 0-2% TiO2, and / or 0-3% ZrO2, and / or 0-7% Na2O, and / or 0-5% Li2O, and / or 0-5% Ln2O3, and / or 0-2% WO3, and / or 0-3% Ta2O5, and / or 0-2% Bi2O3, and / or 0- The optical glass according to (1), further comprising 8% RO, and / or 0-5% ZnO, and / or 0-3% P2O5, and / or 0-1% of a fining agent, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, the RO is one or more of BaO, SrO, CaO, and MgO, and the fining agent is one or more of Sb2O3, SnO2, and CeO2.

[0008] (3) An optical glass, the components of which include SiO2, B2O3, K2O and F, the components being expressed as percentages by weight, SiO2 / (K2O+F) being 1.2 to 4.5, and the refractive index n d is 1.45~1.51, Abbe number v d is 66-74, transition temperature T g is 490℃ or less, and density ρ is 2.70g / cm 3 The following are optical glasses:

[0009] (4) Its components are, by weight percentage, 50-70% SiO2, and / or 2-18% B2O3, and / or 10-30% K2O, and / or 0-2% Nb2O5, and / or 0-2% TiO2, and / or 0-3% ZrO2, and / or more than 3% but not more than 20% F, and / or 0-5% Al2O3, and / or 0-7% Na2O, and / or 0-5% Li2O, and / or 0-5% Ln2O3, and / or 0-2% WO3, and / or or 0-3% Ta2O5, and / or 0-2% Bi2O3, and / or 0-8% RO, 0-5% ZnO, and / or 0-3% P2O5, and / or 0-1% of a fining agent, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, the RO is one or more of BaO, SrO, CaO, and MgO, and the fining agent is one or more of Sb2O3, SnO2, and CeO2.

[0010] (5) The ingredient, expressed as a percentage by weight, meets one or more of the following five criteria: 1) F / B2O3 is 0.2 to 5.0, preferably F / B2O3 is 0.3 to 2.0, more preferably F / B2O3 is 0.4 to 1.5, and even more preferably F / B2O3 is 0.5 to 0.9; 2) Al2O3 / F is 1.0 or less, preferably Al2O3 / F is 0.8 or less, more preferably Al2O3 / F is 0.01 to 0.5, and even more preferably Al2O3 / F is 0.07 to 0.3; 3) K2O / F is 0.7 to 7.0, preferably, K2O / F is 1.0 to 5.0, more preferably, K2O / F is 1.5 to 3.0, and even more preferably, K2O / F is 1.8 to 2.8; 4) SiO2 / (K2O+F) is 1.3 to 3.5, preferably SiO2 / (K2O+F) is 1.5 to 3.0, and more preferably SiO2 / (K2O+F) is 1.7 to 2.5; 5) The optical glass according to any one of (1) to (4), wherein (ZrO2+Nb2O5+TiO2) / F is 0.01 to 1.0, preferably, (ZrO2+Nb2O5+TiO2) / F is 0.01 to 0.8, more preferably, (ZrO2+Nb2O5+TiO2) / F is 0.02 to 0.6, and even more preferably, (ZrO2+Nb2O5+TiO2) / F is 0.03 to 0.4.

[0011] (6) The components are expressed as weight percentages, and (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is greater than 0 and equal to or less than 0.8, preferably, (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01 to 0.5, more preferably, (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01 to 0.3, and even more preferably , (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.02 to 0.2, and / or (Nb2O5+TiO2) / Al2O3 is 2.0 or less, preferably (Nb2O5+TiO2) / Al2O3 is 0.01 to 1.5, more preferably (Nb2O5+TiO2) / Al2O3 is 0.05 to 1.0, and further preferably (Nb2O5+TiO2) / Al2O3 is 0.1 to 0.5, and / or (Li2O+Na2O+K2O) / B2O3 is 0.7 to 6.0, preferably (Li2O+Na2O+K2O) / B2O3 is 0.8 to 5.0, more preferably (Li2O+Na2O+K2O) / B2O3 is 1.0 to 3.0, and even more preferably (Li2O+Na2O+K2O) / B2O3 is 1.5 to 2.0, and / or The optical glass according to any one of (1) to (4), wherein (Li2O+Na2O+K2O) / SiO2 is 0.15 to 0.8, preferably (Li2O+Na2O+K2O) / SiO2 is 0.18 to 0.7, more preferably (Li2O+Na2O+K2O) / SiO2 is 0.2 to 0.6, and even more preferably (Li2O+Na2O+K2O) / SiO2 is 0.2 to 0.45.

[0012] (7) The components are expressed in weight percentage, and SiO2 is 52-68%, preferably SiO2 is 54-64%, and / or B2O3 is 4-16%, preferably B2O3 is 8-14%, and / or K2O is 12-27%, preferably K2O is 13-25%, and / or Nb2O5 is 0-1%, preferably Nb2O5 is 0-0.8%, and / or TiO2 is 0-1%, preferably TiO2 is 0-0.8%. .8%, and / or ZrO2 is 0-2%, preferably ZrO2 is 0-1%, and / or F is 5-16%, preferably F is 6-12%, and / or Al2O3 is 0.1-3%, preferably Al2O3 is 0.2-2%, and / or Na2O is 0-5%, preferably Na2O is 0-3%, and / or Li2O is 0-4%, preferably Li2O is 0-3%, and / or Ln2O3 is 0. 0-3%, preferably Ln2O3 is 0-1%, and / or WO3 is 0-1%, preferably WO3 is 0-0.5%, and / or Ta2O5 is 0-2%, preferably Ta2O5 is 0-1%, and / or Bi2O3 is 0-1%, preferably Bi2O3 is 0-0.5%, and / or RO is 0-5%, preferably RO is 0-2%, and / or ZnO is 0-2%, preferably ZnO is 1 %, and / or P2O5 is 0 to 2%, preferably P2O5 is 0 to 1%, and / or the fining agent is 0 to 0.5%, preferably the fining agent is 0 to 0.2%, said Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3; RO is one or more of BaO, SrO, CaO, and MgO; and the fining agent is one or more of Sb2O3, SnO2, and CeO2.

[0013] (8) The optical glass according to any one of (1) to (4), wherein the components do not contain Na2O, and / or Li2O, and / or La2O3, and / or Gd2O3, and / or Y2O3, and / or Yb2O3, and / or ZnO, and / or P2O5, and / or BaO, and / or SrO, and / or CaO, and / or MgO.

[0014] (9) Refractive index n of optical glass d is 1.45 to 1.51, preferably 1.46 to 1.50, and more preferably 1.47 to 1.49, and the Abbe number v d is 66 to 74, preferably 68 to 72, and more preferably 69 to 71.

[0015] (10) The transmittance τ of the optical glass at 365 nm 365nm is 98.0% or more, preferably 99.0% or more, more preferably 99.5% or more, and / or the ultraviolet ray attenuation resistance performance Δτ of the transmittance at 365 nm 365nm is 1.0% or less, preferably 1.0% or less, more preferably 0.8% or less, and / or the ultraviolet ray attenuation resistance Δτ of the transmittance at 405 nm 405nm is 0.5% or less, preferably 0.3% or less, more preferably 0.2% or less, and / or the bubble degree is A grade or more, preferably A0 grade or more, more preferably A 00 and / or the striae are Class C or higher, preferably Class B or higher, and / or the weather resistance CR is Class 2 or higher, preferably Class 1, and / or the transition temperature T g is 490° C. or less, preferably 480° C. or less, more preferably 475° C. or less, and / or the wear degree F A is 60 to 90, preferably 65 to 85, more preferably 70 to 80, and / or the density ρ is 2.70 g / cm 3or less, preferably 2.60 g / cm 3 More preferably, it is 2.50 g / cm 3 and / or the refractive index batch stability is less than or equal to -15 x 10 -5 ~+15×10 -5 and preferably, −10×10 -5 ~+10×10 -5 and more preferably, -5×10 -5 ~+5×10 -5 and more preferably, −2×10 -5 ~+2×10 -5 The optical glass according to any one of (1) to (4),

[0016] (11) A glass preform produced from the optical glass according to any one of (1) to (10).

[0017] (12) An optical component manufactured from the optical glass according to any one of (1) to (10) or the glass preform according to (11).

[0018] (13) An optical instrument comprising the optical glass according to any one of (1) to (10) and / or the optical component according to (12).

[0019] The beneficial effects of the present invention are as follows: Through the rational design of components, the optical glass of the present invention not only has the desired refractive index and Abbe number, but also has a lower transition temperature and density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, the optical glass of the present invention will be described in detail, but the present invention is not limited to the following embodiments, and can be modified as appropriate within the scope of the object of the present invention. Note that, although duplicated descriptions may be omitted as appropriate, the gist of the present invention is not limited thereto, and in the following description, the optical glass of the present invention may be simply referred to as glass.

[0021] Photolithography lenses in photolithography equipment use radiation-resistant optical glass with a refractive index of 1.45-1.51 and an Abbe number of 66-74, the precision of which determines the precision of the lenses in photolithography equipment. Optical components made of ordinary optical glass will experience a significant decrease in transmittance and a change in refractive index due to long-term irradiation in the ultraviolet band (355-430 nm), which is fatal to all kinds of photolithography equipment operating in the ultraviolet band. As chip manufacturing technology and advanced packaging technology develop toward finer line widths and higher efficiency, photolithography equipment operating in this band will require higher resolution, higher light flux, and larger exposure area. Therefore, the optical materials used in such photolithography equipment are required to have larger dimensions, better radiation resistance, transmittance, and optical uniformity. The main problems with this kind of optical material in the prior art are as follows: The UV resistance is poor, and under the verification conditions of the photolithography equipment, the transmittance attenuation may reach 5%, while the transmittance at 365 nm of this type of material is low, making it difficult to meet the requirements of high-precision photolithography equipment. In some embodiments, the transmittance at 365 nm of the optical glass of the present invention (τ 365nm ) is 98.0% or more, preferably 99.0% or more, and more preferably 99.5% or more, and the ultraviolet ray attenuation resistance performance (Δτ 365nm ) is 1.0% or less, preferably 0.9% or less, and more preferably 0.8% or less, and the ultraviolet ray attenuation resistance performance (Δτ 405nm ) is 0.5% or less, preferably 0.3% or less, and more preferably 0.2% or less. The optical glass of the present invention can also be used in areas such as chip manufacturing and advanced packaging.

[0022] [Optical glass] The range of each component (composition) of the optical glass of the present invention will be explained below. In the present invention, unless otherwise specified, the content of each component and the total content are all expressed in weight percentage (wt%). In the present invention, the components other than the F (fluorine) component are expressed as 100% when the sum of the weight percentage of all oxide components in the glass and the weight percentage of the F component in the glass is 100%.

[0023] Unless otherwise indicated in a particular instance, the numerical ranges recited in the present invention include upper and lower limits, and "greater than" and "less than" include the boundaries and all integers and fractions contained within the range, and are not limited to the specific values ​​recited when the range is defined. The term "and / or" as used herein is inclusive, e.g., "A and / or B" means A only, B only, or both A and B.

[0024] <Required and optional ingredients> SiO2 is the main network-forming component of the glass of the present invention. If the SiO2 content is less than 50%, the transmittance of the glass at 365 nm will be low, which is fatal for ultraviolet optical systems with long optical paths and high illumination requirements, such as the lenses of photolithography equipment and the prisms of exposure machines. Therefore, the lower limit of the SiO2 content is 50%, preferably the lower limit is 52%, and more preferably the lower limit is 54%. If the SiO2 content exceeds 70%, it is difficult for the refractive index of the glass to meet the design requirements, and at the same time, the glass needs to be melted at a higher temperature. With increasing smelting temperature, the erosion of the crucible by the glass liquid increases exponentially, and the content of ions with strong absorption in the ultraviolet band, such as iron (Fe) ions and platinum (Pt) ions, increases rapidly, causing a rapid decrease in the transmittance of ultraviolet light, especially the transmittance at 365 nm. In addition, if the SiO2 content is too high, the high-temperature viscosity of the glass becomes too high, making it difficult to meet design requirements such as optical uniformity, bubble degree, and striae. Therefore, the upper limit of the SiO2 content is 70%, preferably the upper limit is 68%, and more preferably the upper limit is 64%.

[0025] An appropriate amount of B2O3 can increase the refractive index of glass, strengthen the structure of glass, and improve the melting property and ultraviolet resistance of glass. If the content of B2O3 exceeds 18%, the erosion of the crucible by the glass liquid increases rapidly, and the transmittance of ultraviolet light decreases rapidly. If the content of B2O3 is less than 2%, the glass becomes difficult to melt. Therefore, the content of B2O3 is 2 to 18%, preferably 4 to 16%, and more preferably 8 to 14%.

[0026] Although Al2O3 can increase the density of the internal structure of glass and improve the transmittance of ultraviolet light and the chemical stability of glass, if the content exceeds 5%, stones are likely to be generated inside the glass, and the internal quality of the glass deteriorates. Therefore, the content of Al2O3 is 0 to 5%, preferably 0.1 to 3%, and more preferably 0.2 to 2%.

[0027] ZrO2 improves the devitrification resistance of glass, improves the chemical stability and mechanical properties of glass, reduces the erosion of the crucible material during the melting process, and increases the ultraviolet transmittance of glass. If the content is too high, it becomes more difficult to melt the glass, the smelting temperature increases, inclusions are generated inside the glass, and the light transmittance decreases. Therefore, the content of ZrO2 in the present invention is 0-3%, preferably 0-2%, and more preferably 0-1%.

[0028] K2O can improve the thermal stability and melting property of glass, lower the effect of transition temperature, and also reduce the high-temperature viscosity of glass, provide free oxygen to strengthen the network structure of glass, and thereby increase the ultraviolet transmittance of glass. However, if its content is too high, the devitrification resistance and chemical stability of glass are reduced. Therefore, the content of K2O in the present invention is 10-30%, preferably 12-27%, and more preferably 13-25%.

[0029] Na2O can improve the meltability of glass and lower the liquidus temperature of glass, but if the content is too high, it promotes a decrease in the crystallization resistance of glass and lengthens the time it takes for glass to change from liquid to solid during cooling and forming, making crystallization more likely to proceed. Therefore, the content of Na2O in the present invention is 0 to 7%, preferably 0 to 5%, and more preferably 0 to 3%. In some embodiments, it is even more preferable that Na2O is not included.

[0030] Li2O can effectively lower the glass transition temperature, but optical glass is usually smelted using a platinum or platinum alloy container, and in the high-temperature smelting process, Li in the glass components is likely to corrode the platinum or platinum alloy container, resulting in a large amount of platinum-containing foreign matter in the finished glass product, which results in a decrease in the ultraviolet light transmittance of the glass. Therefore, the content of Li2O in the present invention is 0 to 5%, preferably 0 to 4%, and more preferably 0 to 3%. In some embodiments, it is even more preferable that the glass does not contain Li2O.

[0031] In some embodiments, the ratio (Li2O+Na2O+K2O) / B2O3 of the total content of Li2O, Na2O, and K2O (Li2O+Na2O+K2O) to the content of B2O3 can be controlled within the range of 0.7 to 6.0 to improve the ultraviolet transmittance and the batch stability of the refractive index of the glass, and the batch stability of the refractive index is very important for photolithography equipment. Therefore, preferably, (Li2O+Na2O+K2O) / B2O3 is 0.7 to 6.0, more preferably, (Li2O+Na2O+K2O) / B2O3 is 0.8 to 5.0, even more preferably, (Li2O+Na2O+K2O) / B2O3 is 1.0 to 3.0, and even more preferably, (Li2O+Na2O+K2O) / B2O3 is 1.5 to 2.0.

[0032] In some embodiments, when the ratio (Li2O+Na2O+K2O) / SiO2 of the total content of Li2O, Na2O, and K2O (Li2O+Na2O+K2O) to the content of SiO2 is controlled within the range of 0.15 to 0.8, the volatilization of F in the glass can be suppressed, the batch stability of the refractive index of the glass can be improved, and the transition temperature of the glass can be lowered. Therefore, preferably, (Li2O+Na2O+K2O) / SiO2 is 0.15 to 0.8, and more preferably, (Li2O+Na2O+K2O) / SiO2 is 0.18 to 0.7. Furthermore, when (Li2O+Na2O+K2O) / SiO2 is controlled within the range of 0.2 to 0.6, the abrasion resistance, high-temperature viscosity, and weather resistance of the glass can be optimized to more appropriate ranges. Therefore, more preferably, (Li2O+Na2O+K2O) / SiO2 is 0.2 to 0.6, and even more preferably, (Li2O+Na2O+K2O) / SiO2 is 0.2 to 0.45.

[0033] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3) is a component that can improve the refractive index and chemical stability of glass. By setting the content of Ln2O3 to 5% or less, it is possible to prevent the deterioration of the devitrification resistance of the glass and to prevent the refractive index and Abbe number of the glass from exceeding the design requirements. Therefore, the content of Ln2O3 is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is more preferable that the glass does not contain La2O3, and / or does not contain Gd2O3, and / or does not contain Y2O3, and / or does not contain Yb2O3.

[0034] Nb2O5, TiO2, Bi2O3, Ta2O5, and WO3 are oxides with high refractive index and high dispersion, and when used in glass, the ultraviolet resistance of the glass is improved, and at the same time, the refractive index and dispersion of the glass are improved. However, when the content of the above oxides is high, the ultraviolet transmittance of the glass is reduced. Therefore, the content of Nb2O5 in the present invention is 0 to 2%, preferably 0 to 1%, and more preferably 0 to 0.8%. The content of TiO2 is 0 to 2%, preferably 0 to 1%, and more preferably 0 to 0.8%. The content of Bi2O3 is 0 to 2%, preferably 0 to 1%, and more preferably 0 to 0.5%. The content of WO3 is 0 to 2%, preferably 0 to 1%, and more preferably 0 to 0.5%. The content of Ta2O5 is 0 to 3%, preferably 0 to 2%, and more preferably 0 to 1%.

[0035] In some embodiments, by controlling the ratio of the total content of Nb2O5, TiO2, Bi2O3, Ta2O5, and WO3 (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) to the content of B2O3 (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 within a range of more than 0 and not more than 0.8, it is possible to improve the UV resistance of the glass, prevent a decrease in the UV transmittance of the glass, and optimize the bubble degree and refractive index batch stability of the glass. Therefore, preferably, (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is more than 0 and not more than 0.8, more preferably, (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01 to 0.5, even more preferably, (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.01 to 0.3, and even more preferably, (Nb2O5+TiO2+Bi2O3+Ta2O5+WO3) / B2O3 is 0.02 to 0.2.

[0036] In some embodiments, when the ratio (Nb2O5+TiO2) / Al2O3 of the total content of Nb2O5 and TiO2 (Nb2O5+TiO2) to the content of Al2O3 is controlled to 2.0 or less, the ultraviolet resistance performance of the glass can be improved and the density of the glass can be prevented from increasing at the same time. Therefore, preferably, (Nb2O5+TiO2) / Al2O3 is 2.0 or less, and more preferably, (Nb2O5+TiO2) / Al2O3 is 0.01 to 1.5. Furthermore, when (Nb2O5+TiO2) / Al2O3 is controlled in the range of 0.05 to 1.0, the wear degree and striae of the glass can be further optimized. Therefore, more preferably, (Nb2O5+TiO2) / Al2O3 is 0.05 to 1.0, and even more preferably, (Nb2O5+TiO2) / Al2O3 is 0.1 to 0.5.

[0037] Alkaline earth metal oxides RO (RO is one or more of BaO, SrO, CaO, and MgO) adjust the optical constants and high temperature viscosity of glass, but if the content is high, it reduces the ultraviolet transmittance and chemical properties of the glass. Therefore, the content of RO is 0 to 8%, preferably 0 to 5%, and more preferably 0 to 2%. In some embodiments, it is further preferable that the glass does not contain BaO, and / or does not contain SrO, and / or does not contain CaO, and / or does not contain MgO.

[0038] ZnO can strengthen the network structure of the glass and improve the refractive index and ultraviolet transmittance of the glass. If the content of ZnO is too high, the glass is prone to phase separation, the ultraviolet transmittance decreases, and the striae become poor. Therefore, the content of ZnO is 0 to 5%, preferably 0 to 2%, and more preferably less than 1%. In some embodiments, it is more preferable that the glass does not contain ZnO.

[0039] P2O5 has the effect of lowering the melting temperature of glass raw materials and increasing the ultraviolet transmittance of glass, but if its content increases, the crystallization prevention performance and chemical stability of glass decrease. Therefore, the content of P2O5 is 0 to 3%, preferably 0 to 2%, and more preferably 0 to 1%. In some embodiments, it is more preferable that P2O5 is not contained.

[0040] In the present invention, by containing 0 to 1% of one or more of Sb2O3, SnO2, and CeO2 as a fining agent, the fining effect of the glass can be improved and the bubble degree of the glass can be increased. Preferably, the content of the fining agent is 0 to 0.5%, more preferably, the content of the fining agent is 0 to 0.2%. Since the optical glass of the present invention has a rational design of the component types and contents and has an excellent bubble degree, in some embodiments, it is more preferable that the glass does not contain a fining agent. If the content of Sb2O3 exceeds 1%, the fining performance of the glass tends to decrease, and at the same time, its strong oxidizing effect promotes corrosion of platinum or platinum alloy containers for glass melting and deterioration of molding dies. Therefore, in the present invention, the content of Sb2O3 is preferably 0 to 1%, more preferably 0 to 0.5%, even more preferably 0 to 0.2%, and even more preferably does not contain Sb2O3. SnO2 can also be used as a clarifier, but if its content exceeds 1%, the glass tends to be colored, or when the glass is heated and softened and reshaped by press molding, Sn becomes the starting point for crystal nucleation and devitrification is likely to occur. Therefore, the content of SnO2 in the present invention is 0 to 1%, more preferably 0 to 0.5%, even more preferably 0 to 0.2%, and even more preferably does not contain SnO2. The function and content ratio of CeO2 are the same as those of SnO2, and its content is preferably 0 to 1%, more preferably 0 to 0.5%, even more preferably 0 to 0.2%, and even more preferably does not contain CeO2.

[0041] F (fluorine) can lower the glass transition temperature and improve the ultraviolet transmittance and ultraviolet resistance of glass. If the F content is too high, volatilization during the glass smelting process increases, causing fluctuations in the refractive index and the inherent quality of the glass (striae, bubble degree), while at the same time causing the optical uniformity of the glass to not meet the design requirements, and adversely affecting the production environment and the health of workers. Therefore, the F content is more than 3% and not more than 20%, preferably 5 to 16%, and more preferably 6 to 12%.

[0042] In some embodiments, when the ratio F / B2O3 of the content of F to the content of B2O3 is controlled in the range of 0.2 to 5.0, the ultraviolet transmittance of the glass can be improved and the deterioration of the ultraviolet resistance performance can be prevented. Therefore, F / B2O3 is preferably 0.2 to 5.0, and more preferably F / B2O3 is 0.3 to 2.0. Furthermore, when F / B2O3 is controlled in the range of 0.4 to 1.5, the bubble degree and abrasion degree of the glass can be further optimized. Therefore, F / B2O3 is more preferably 0.4 to 1.5, and even more preferably F / B2O3 is 0.5 to 0.9.

[0043] In some embodiments, by controlling the ratio Al2O3 / F of the Al2O3 content to the F content to 0.1 or less, it is possible to prevent a decrease in the ultraviolet transmittance and weather resistance of the glass. Therefore, Al2O3 / F is preferably 1.0 or less, and more preferably 0.8 or less. Furthermore, by controlling Al2O3 / F to a range of 0.01 to 0.5, it is possible to further improve the striae of the glass. Therefore, more preferably, Al2O3 / F is 0.01 to 0.5, and even more preferably, Al2O3 / F is 0.07 to 0.3.

[0044] In some embodiments, controlling the ratio K2O / F of the K2O content to the F content in the range of 0.7 to 7.0 helps to improve the striae and UV resistance of the glass, and improve the refractive index batch stability of the glass. Therefore, K2O / F is preferably 0.7 to 7.0, more preferably 1.0 to 5.0, even more preferably 1.5 to 3.0, and still more preferably 1.8 to 2.8.

[0045] In some embodiments, the ratio SiO2 / (K2O+F) of the content of SiO2 to the total content K2O and F (K2O+F) is controlled to a range of 1.2 to 4.5, which helps the glass to obtain an appropriate wear degree and transition temperature. Therefore, preferably, SiO2 / (K2O+F) is 1.2 to 4.5, and more preferably, SiO2 / (K2O+F) is 1.3 to 3.5. Furthermore, by controlling SiO2 / (K2O+F) to a range of 1.5 to 3.0, the bubble degree and ultraviolet transmittance of the glass can be further increased. Therefore, more preferably, SiO2 / (K2O+F) is 1.5 to 3.0, and even more preferably, SiO2 / (K2O+F) is 1.7 to 2.5.

[0046] In some embodiments, the ratio (ZrO2+Nb2O5+TiO2) / F of the total content (ZrO2+Nb2O5+TiO2) of ZrO2, Nb2O5, and TiO2 to the content of F is controlled within the range of 0.01 to 1.0, and the glass has excellent ultraviolet resistance and low transition temperature, and at the same time, has an appropriate wear resistance. Therefore, preferably, (ZrO2+Nb2O5+TiO2) / F is 0.01 to 1.0, more preferably, (ZrO2+Nb2O5+TiO2) / F is 0.01 to 0.8, even more preferably, (ZrO2+Nb2O5+TiO2) / F is 0.02 to 0.6, and even more preferably, (ZrO2+Nb2O5+TiO2) / F is 0.03 to 0.4.

[0047] <Ingredients that should not be included> In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are contained alone or in small amounts in combination, the glass is colored and absorption occurs at specific wavelengths in the visible light region, thereby weakening the visible light transmittance improving effect of the present invention. Therefore, in optical glasses that require transmittance at wavelengths in the visible light region, in particular, it is preferable to contain substantially no oxides of these metals.

[0048] Oxides of Th, Cd, Tl, Os, Be, and Se have recently been restricted as harmful chemical substances not only in the glass manufacturing process but also in the processing process and post-production treatment, and it is necessary to take measures for environmental protection. Therefore, when the impact on the environment is important, it is preferable that the optical glass is substantially free of these substances, except for unavoidable contamination. As a result, the optical glass is substantially free of substances that pollute the environment. Therefore, the optical glass of the present invention can be manufactured, processed, and disposed of without taking special environmental measures.

[0049] From the viewpoint of environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.

[0050] The terms "free" and "0%" used in this specification mean that the compound, molecule or element is not intentionally added as a raw material for the optical glass of the present invention. However, impurities or components that are not intentionally added may exist as raw materials and / or manufacturing equipment for the optical glass, and may be contained in small or trace amounts in the final optical glass, and this situation is also within the scope of protection of the patent of the present invention.

[0051] The performance of the optical glass of the present invention will now be described.

[0052] <Refractive index and Abbe number> The refractive index of optical glass (n d ) and Abbe number (ν d ) is tested in accordance with the method specified in "GB / T7962.1-2010".

[0053] In some embodiments, the refractive index (nd ) is 1.45, preferably 1.46, and more preferably 1.47. In some embodiments, the refractive index (n d ) is 1.51, preferably the upper limit is 1.50, and more preferably the upper limit is 1.49.

[0054] In some embodiments, the Abbe number (ν d ) is 66, preferably, the lower limit is 68, and more preferably, the lower limit is 69. In some embodiments, the Abbe number (ν d ) is 74, preferably the upper limit is 72, and more preferably the upper limit is 71.

[0055] Transmittance τ at <365 nm 365nm > The ultraviolet transmittance of the optical glass of the present invention is characterized by the transmittance at 365 nm, and the transmittance at 365 nm (τ 365nm ) is tested according to the method specified in "GB / T7962.12-2010", and the thickness of the glass sample is 10 mm.

[0056] In some embodiments, the transmittance at 365 nm (τ 365nm ) is 98.0% or more, preferably 99.0% or more, and more preferably 99.5% or more.

[0057] <UV resistance> The UV resistance of optical glass is Δτ 365nm or Δτ 405nm and Δτ 365nm is the UV attenuation resistance performance of the transmittance at 365 nm, and Δτ 405nm is the UV attenuation resistance performance of the transmittance at 405 nm, and Δτ 365nm or Δτ 405nm The lower the value, the better the UV resistance of the glass.

[0058] Δτ 365nm The test method is as follows: The original transmittance τ of the sample at 365 nm is measured according to the method specified in "GB / T7962.12-2010". 365nm-1 The test was performed using a high-pressure mercury lamp, and the power density on the glass surface was 1 W / cm 2 After 2 hours of irradiation, the transmittance τ365nm-2 at 365nm was tested again according to the method specified in "GB / T7962.12-2010", and the difference τ 365nm-1 -τ 365nm-2 is the attenuation of the glass at that wavelength, and the thickness of the glass sample is 10 mm.

[0059] In some embodiments, the UV attenuation resistance (Δτ 365nm ) is 1.0% or less, preferably 0.9% or less, and more preferably 0.8% or less.

[0060] Δτ 405nm The test method is as follows: The original transmittance τ of the sample at 405 nm is measured according to the method specified in "GB / T7962.12-2010". 405nm-1 The test was performed using a high-pressure mercury lamp, and the power density on the glass surface was 1 W / cm 2 After 2 hours of irradiation, the transmittance τ at 405 nm was measured according to the method specified in GB / T7962.12-2010. 405nm-2 The difference between the two tests, τ 405nm-1 -τ 405nm-2 is the attenuation of the glass at that wavelength, and the thickness of the glass sample is 10 mm.

[0061] In some embodiments, the UV attenuation resistance (Δτ 405nm ) is 0.5% or less, preferably 0.3% or less, and more preferably 0.2% or less.

[0062] <Bubble level> The bubble content of optical glass is tested and classified according to the method specified in "GB / T7962.8-2010".

[0063] In some embodiments, the bubble degree of the optical glass of the present invention is Class A or higher, preferably Class A0 or higher, and more preferably Class A or higher. 00 It is of class.

[0064] <Striae> The test method for striae in optical glass is as follows: A point light source and a lens are used to create a striae measuring device, and the striae are compared with a standard sample from the direction in which they are most visible, and classified into four grades according to Table 1.

[0065] [Table 1]

[0066] In some embodiments, the striae of the optical glasses of the present invention are Class C or better, and preferably Class B or better.

[0067] <Weather resistance> The weather resistance (CR) test method for optical glass is as follows: A sample is placed in a test box with a relative humidity of 90% and a saturated water vapor environment, and 15 cycles are performed alternately at 40 to 50°C every hour. Weather resistance types are classified according to the change in turbidity before and after the sample is placed in the box, and the weather resistance classifications are shown in Table 2.

[0068] [Table 2]

[0069] In some embodiments, the weatherability (CR) of the optical glass of the present invention is Class 2 or higher, and preferably Class 1.

[0070] <Transition temperature> Transition temperature of optical glass (T g ) is tested in accordance with the method specified in "GB / T7962.16-2010".

[0071] In some embodiments, the transition temperature (T g ) is 490°C or less, preferably 480°C or less, and more preferably 475°C or less.

[0072] <Wear level> Wear rate of optical glass (F A ) refers to the ratio of the wear volume of the sample to the wear volume (volume) of a standard sample (H-K9 glass) under exactly the same conditions, multiplied by 100, and the formula is given as follows:

[0073] F A =V / V0×100=(W / ρ) / (W0 / ρ0)×100 Wherein, V is the volumetric wear volume of the test sample, V0 - volumetric wear volume of standard sample, W - mass wear of the test sample, W0 - mass wear volume of standard sample, ρ - density of the sample under test, ρ0 - density of the standard sample.

[0074] In some embodiments, the abrasion rate (F A ) is 60, preferably the lower limit is 65, and more preferably the lower limit is 70.

[0075] In some embodiments, the abrasion rate (F A ) is 90, preferably the upper limit is 85, and more preferably the upper limit is 80.

[0076] <density> The density (ρ) of optical glass is tested according to the method specified in "GGB / T7962.20-2010".

[0077] In some embodiments, the density (ρ) of the optical glass of the present invention is 2.70 g / cm 3or less, preferably 2.60 g / cm 3 More preferably, 2.50 g / cm 3 The following is the result.

[0078] <Refractive index batch stability> The test method for the refractive index batch stability of optical glass is as follows: Using the same glass compounding method, manufacturing method, and equipment, melt the glass twice to obtain the first and second melted glasses. Then, according to the method specified in "GB / T7962.1-2010", the refractive index n d1回目 and the refractive index of the second glass, n d2回目 Test each of n d1回目 -n d2回目 is the refractive index batch stability of the glass material.

[0079] In some embodiments, the refractive index batch stability of the optical glasses of the present invention is -15×10 -5 ~+15×10 -5 and preferably, −10×10 -5 ~+10×10 -5 and more preferably, -5×10 -5 ~+5×10 -5 and more preferably 2×10 -5 ~+2×10 -5 It is.

[0080] [Method of manufacturing optical glass] The manufacturing method of the optical glass of the present invention is as follows. The glass of the present invention is produced by ordinary raw materials and ordinary processes, using carbonates, nitrates, sulfates, phosphates, metaphosphates, hydroxides, oxides, fluorides, etc. as raw materials, and blending them according to ordinary methods, and then putting the blended furnace charge into a smelting furnace (such as platinum crucibles and quartz crucibles) at 1200 to 1450 ° C. to melt, clarify, stir, and homogenize, and obtain a homogeneous molten glass without bubbles and unmelted residues, and then pouring the molten glass into a mold and annealing. Those skilled in the art can appropriately select the raw materials, processing methods, and processing parameters according to actual needs.

[0081] [Glass preforms and optical components] For example, a glass preform can be manufactured from the manufactured optical glass using direct drop molding, grinding, or stamping molding such as hot press molding. That is, the glass preform is manufactured by directly precision drop molding molten optical glass into a glass precision preform, or by mechanical processing such as polishing or grinding, or by manufacturing a preform material for stamping molding from optical glass, reheating and press molding the preform material, and then grinding to manufacture the glass preform. It should be noted that the manufacturing means of the glass preform is not limited to the above means.

[0082] As described above, the optical glass of the present invention is useful for various optical components and optical designs, but preferably, a preform material is formed from the optical glass of the present invention, and this preform material is used for reheat press molding, precision stamping molding, or the like to manufacture components such as lenses and prisms.

[0083] The glass preform and optical component of the present invention are both formed from the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass, and the optical component of the present invention has the excellent properties of optical glass, and can provide various optical components such as lenses and prisms with high optical value.

[0084] Examples of the lens include various lenses whose lens surfaces are spherical or aspherical, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.

[0085] [Optical equipment] Optical components formed from the optical glass of the present invention can be used in the manufacture of optical instruments such as photography equipment, video recording equipment, projection equipment, display equipment, mask aligners, vehicle-mounted equipment, and surveillance equipment.

[0086] (Example) <Examples of optical glass> In order to further clearly describe and explain the technical solutions of the present invention, the following non-limiting examples are provided.

[0087] In the present examples, the above-mentioned optical glass manufacturing method is used to obtain optical glasses having the compositions shown in Tables 3 to 5. The properties of each glass are tested according to the test methods described in the present invention, and the test results are shown in Tables 3 to 5.

[0088] [Table 3-1]

[0089] [Table 3-2]

[0090] [Table 4-1]

[0091] [Table 4-2]

[0092] [Table 5-1]

[0093] [Table 5-2]

[0094] <Example of glass preform> The glasses obtained in Examples 1 to 21 of the optical glass are used to manufacture preforms such as various lenses, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, and prisms, for example, by grinding, or stamping molding means such as reheat press molding or precision stamping molding.

[0095] <Examples of optical components> These preforms, obtained from the glass preform examples above, are annealed to reduce the internal stress in the glass while fine tuning the refractive index and other optical properties to reach the required values.

[0096] Each preform is then ground to produce a variety of lenses or prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, plano-concave lenses, etc. The surfaces of the resulting optical components can also be coated with an anti-reflective coating.

[0097] <Examples of optical equipment> Optical components manufactured according to the above optical component embodiments may be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / illumination in the automotive field, photolithography technology, excimer lasers, wafers, computer chips and integrated circuits and electronic devices containing such circuits and chips through optical design and by using one or more optical components to form optical members or optical assemblies.

Claims

1. Optical glass, the composition of which is, by weight percentage, 50 to 70% SiO 2 , 2-18% B 2 O 3 , 10-30% K 2 Contains O and more than 3% to 20% F, and SiO 2 / (K 2 O+F) is 1.2 to 4.

5.

2. The composition is, by weight percentage, 0 to 5% Al. 2 O 3 and / or 0-2% Nb 2 O 5 and / or 0 to 2% TiO 2 and / or 0 to 3% ZrO 2 and / or 0 to 7% Na 2 O, and / or 0-5% Li 2 O, and / or 0-5% Ln 2 O 3 , and / or 0-2% WO 3 and / or 0 to 3% Ta 2 O 5 and / or 0 to 2% Bi 2 O 3 , and / or 0-8% RO, and / or 0-5% ZnO, and / or 0-3% P 2 O 5 and / or 0 to 1% of a fining agent, 2 O 3 Is La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 RO is one or more of BaO, SrO, CaO, MgO, and the fining agent is Sb 2 O 3 , SnO 2 , CeO 2 2. The optical glass according to claim 1, characterized in that it is one or more of the following:

3. Optical glass, the components of which are SiO 2 , B 2 O 3 , K 2 O and F, the components being expressed in weight percentages, and SiO 2 / (K 2 O+F) is 1.2 to 4.5, and the refractive index n d is 1.45 to 1.51, Abbe number v d is 66 to 74, transition temperature T g is 490°C or less, and density ρ is 2.70 g / cm 3 An optical glass characterized in that:

4. The components are, by weight percentage, 50 to 70% SiO 2 , and / or 2 to 18% B 2 O 3 , and / or 10 to 30% K 2 O, and / or 0-2% Nb 2 O 5 and / or 0 to 2% TiO 2 and / or 0 to 3% ZrO 2 , and / or more than 3% to 20% F, and / or 0 to 5% Al 2 O 3 and / or 0 to 7% Na 2 O, and / or 0-5% Li 2 O, and / or 0-5% Ln 2 O 3 , and / or 0-2% WO 3 and / or 0 to 3% Ta 2 O 5 and / or 0 to 2% Bi 2 O 3 , and / or 0-8% RO, 0-5% ZnO, and / or 0-3% P2O5, and / or 0-1% fining agent, 2 O 3 Is La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 RO is one or more of BaO, SrO, CaO, MgO, and the fining agent is Sb 2 O 3 , SnO 2 , CeO 2 4. The optical glass according to claim 3, characterized in that it is one or more of the following:

5. The ingredients, expressed as weight percentages, meet one or more of the following five conditions: 1) F / B 2 O 3 is 0.2 to 5.0, and preferably F / B 2 O 3 is 0.3 to 2.0, and more preferably F / B 2 O 3 is 0.4 to 1.5, and more preferably F / B 2 O 3 is 0.5 to 0.9, 2) Al 2 O 3 / F is 1.0 or less, and preferably Al 2 O 3 / F is 0.8 or less, and more preferably Al 2 O 3 / F is 0.01 to 0.5, and more preferably Al 2 O 3 / F is 0.07 to 0.3, 3) K 2 O / F is 0.7 to 7.0, preferably K 2 O / F is 1.0 to 5.0, more preferably K 2 O / F is 1.5 to 3.0, and more preferably K 2 O / F is 1.8 to 2.8, 4) SiO 2 / (K 2 O + F) is 1.3 to 3.5, and preferably SiO 2 / (K 2 O + F) is 1.5 to 3.0, and more preferably SiO2 / (K 2 O + F) is 1.7 to 2.5, 5) (ZrO 2 +Nb 2 O 5 + TiO 2 ) / F is 0.01 to 1.0, and preferably (ZrO 2 +Nb 2 O 5 + TiO 2 ) / F is 0.01 to 0.8, and more preferably (ZrO 2 +Nb 2 O 5 + TiO 2 ) / F is 0.02 to 0.6, and more preferably (ZrO 2 +Nb 2 O 5 + TiO 2 5. The optical glass according to claim 1, wherein F / F is 0.03 to 0.

4.

6. The components are expressed in weight percentages: (Nb 2 O 5 + TiO 2 +Bi 2 O 3 +Ta 2 O 5 +W.O. 3 ) / B 2 O 3 is more than 0 and not more than 0.8, and preferably, (Nb 2 O 5 + TiO 2 +Bi 2 O 3 +Ta 2 O 5 +W.O. 3 ) / B 2 O 3 is 0.01 to 0.5, and more preferably (Nb 2 O 5 + TiO 2 +Bi 2 O 3 +Ta 2 O 5 +W.O. 3 ) / B 2 O 3 is 0.01 to 0.3, and more preferably (Nb 2 O 5 + TiO 2 +Bi 2 O 3 +Ta 2 O 5 +W.O. 3 ) / B 2 O 3 is 0.02 to 0.2, and / or (Nb 2 O 5 + TiO 2 ) / Al 2 O 3 is 2.0 or less, and preferably (Nb 2 O 5 + TiO 2 ) / Al 2 O 3 is 0.01 to 1.5, and more preferably (Nb 2 O 5 + TiO 2 ) / Al 2 O 3 is 0.05 to 1.0, and more preferably (Nb 2 O 5 + TiO 2 ) / Al 2 O 3 is 0.1 to 0.5, and / or (Li 2 O+Na 2 O+K 2 O) / B 2 O 3 is 0.7 to 6.0, preferably (Li 2 O+Na 2 O+K 2 O) / B 2 O 3 is 0.8 to 5.0, and more preferably (Li 2 O+Na 2 O+K 2 O) / B 2 O 3 is 1.0 to 3.0, and more preferably (Li 2 O+Na 2 O+K 2 O) / B 2 O 3 is 1.5 to 2.0, and / or (Li 2 O+Na 2 O+K 2 O) / SiO 2 is 0.15 to 0.8, preferably (Li 2 O+Na 2 O+K 2 O) / SiO 2 is 0.18 to 0.7, and more preferably (Li 2 O+Na 2 O+K 2 O) / SiO 2 is 0.2 to 0.6, and more preferably (Li 2 O+Na 2 O+K 2 O) / SiO 2 The optical glass according to any one of claims 1 to 4, wherein is 0.2 to 0.

45.

7. The components are expressed as weight percentages and are: SiO 2 is 52 to 68%, and preferably SiO 2 is 54-64%, and / or B 2 O 3 is 4 to 16%, preferably B 2 O 3 is 8 to 14%, and / or K 2 O is 12 to 27%, and preferably K 2 O is 13 to 25%, and / or Nb 2 O 5 is 0 to 1%, preferably Nb 2 O 5 is 0 to 0.8%, and / or TiO 2 is 0 to 1%, preferably TiO 2 is 0 to 0.8%, and / or ZrO 2 is 0 to 2%, preferably ZrO 2 is 0-1%, and / or F is 5-16%, preferably F is 6-12%, and / or Al 2 O 3 is 0.1 to 3%, and preferably Al 2 O 3 is 0.2 to 2%, and / or Na 2 O is 0 to 5%, preferably Na 2 O is 0 to 3%, and / or Li 2 O is 0 to 4%, preferably Li 2 O is 0 to 3%, and / or Ln 2 O 3 is 0 to 3%, preferably Ln 2 O 3 is 0 to 1%, and / or WO 3 is 0 to 1%, preferably WO 3 is 0 to 0.5%, and / or Ta 2 O 5 is 0 to 2%, preferably Ta 2 O 5 is 0 to 1%, and / or Bi 2 O 3 is 0 to 1%, preferably Bi 2 O 3 is 0-0.5%, and / or RO is 0-5%, preferably RO is 0-2%, and / or ZnO is 0-2%, preferably ZnO is less than 1%, and / or P 2 O 5 is 0 to 2%, and preferably P 2 O 5 is 0 to 1%, and / or the fining agent is 0 to 0.5%, preferably the fining agent is 0 to 0.2%, and the Ln 2 O 3 Is La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 RO is one or more of BaO, SrO, CaO, MgO, and the fining agent is Sb 2 O 3 , SnO 2 , CeO 2 5. The optical glass according to claim 1, wherein the optical glass satisfies one or more of the following conditions:

8. The components are Na 2 Does not contain O and / or Li 2 Does not contain O, and / or does not contain La2O3, and / or does not contain Gd 2 O 3 and / or Y 2 O 3 and / or Yb 2 O 3 and / or does not contain ZnO and / or does not contain P 2 O 5 and / or does not contain BaO, and / or does not contain SrO, and / or does not contain CaO, and / or does not contain MgO.

9. The refractive index n of the optical glass d is 1.45 to 1.51, preferably 1.46 to 1.50, more preferably 1.47 to 1.49, and the Abbe number v d The optical glass according to any one of claims 1 to 4, wherein Mn is 66 to 74, preferably 68 to 72, and more preferably 69 to 71.

10. The transmittance τ of the optical glass at 365 nm 365nm is 98.0% or more, preferably 99.0% or more, more preferably 99.5% or more, and / or the ultraviolet ray attenuation resistance performance Δτ of the transmittance at 365 nm 365nm is 1.0% or less, preferably 1.0% or less, more preferably 0.8% or less, and / or the ultraviolet ray attenuation resistance performance Δτ of the transmittance at 405 nm 405nm is 0.5% or less, preferably 0.3% or less, more preferably 0.2% or less, and / or the bubble degree is A class or more, preferably A 0 More preferably, it is A grade or higher. 00 and / or the striae are class C or higher, preferably class B or higher, and / or the weather resistance CR is class 2 or higher, preferably class 1, and / or the transition temperature T g is 490° C. or less, preferably 480° C. or less, more preferably 475° C. or less, and / or the wear degree F A is 60 to 90, preferably 65 to 85, more preferably 70 to 80, and / or the density ρ is 2.70 g / cm 3 or less, preferably 2.60 g / cm 3 More preferably, 2.50 g / cm 3 and / or the refractive index batch stability is less than or equal to -15×10 -5 ~ +15 x 10 -5 and preferably, −10×10 -5 ~ +10 x 10 -5 and more preferably, −5×10 -5 ~ +5 x 10 -5 and more preferably, −2×10 -5 ~ +2 x 10 -5 5. The optical glass according to claim 1, wherein

11. A glass preform, characterized in that it is made of the optical glass according to any one of claims 1 to 10.

12. An optical component, characterized in that it is made of an optical glass according to any one of claims 1 to 10 or made of a glass preform according to claim 11.

13. Optical instrument, characterized in that it comprises an optical glass according to any one of claims 1 to 10 and / or an optical component according to claim 12.

Citation Information

Patent Citations

  • Optical glass

    CN106116143A

  • Method and apparatus for manufacturing optical glass

    JP2007126296A

  • Optical glass, sample holding tool and optical element

    JP2010083723A

  • Optical glass and optical element

    JP2025026322A